Flexible electrochromic supercapacitor and preparation method thereof
By depositing 3-methylthiophene and tungsten trioxide electrochromic composite materials on the surface of the conductive fibers and coating them with gel electrolyte, the intuitiveness and flexibility of supercapacitors on the fiber materials are solved, and flexible electrochromicity is achieved The color-changing supercapacitor has fast response and excellent capacitance performance, suitable for smart textiles and wearable electronic components.
Patent Information
- Application Number
- CN202411327498.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-10
AI Technical Summary
Existing supercapacitors lack visual energy storage intuitiveness and flexibility when applying fiber materials, making them difficult to widely use in smart textiles and wearable electronic components.
The three-electrode system is used to deposit organic 3-methylthiophene and inorganic tungsten trioxide electrochromic composite materials on the surface of the conductive fibers to form a dense electrochromic layer and completely coated with gel electrolyte to prepare a flexible electrochromic super Capacitor.
It achieves fast response time, stable cycling stability and excellent capacitive performance, and can show color changes at different voltages, which are suitable for the field of smart wearable materials.
Smart Images

Figure CN119296977A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochromic fibers, and in particular to a flexible electrochromic supercapacitor and a preparation method thereof. Background Art
[0002] Supercapacitor is a new type of energy storage device between traditional capacitors and rechargeable batteries, with high power density, long cycle life, safety, reliability and environmental friendliness. Its energy storage principle is mainly to store energy through the rapid reversible chemical reaction between electrode materials and electrolytes. The capacity of supercapacitors is much greater than that of traditional capacitors.
[0003] Electrochromism is achieved by applying a certain voltage to the color-changing material, causing the electrochromic material to undergo an oxidation-reduction reaction, thereby achieving a change in the color of the material.
[0004] By combining electrochromism with supercapacitors, the application of fibers is more extensive. The visualized capacitance performance can intuitively show the level of energy storage. The flexible fibers can also apply supercapacitors to smart textiles and wearable electronic components. Summary of the invention
[0005] The purpose of the present application is to provide a flexible electrochromic supercapacitor and a preparation method thereof, wherein the preparation method uses flexible fibers as a substrate, deposits organic (3-methylthiophene) and inorganic (tungsten trioxide) electrochromic composite materials on the surface of the conductive fibers using a three-electrode system, and forms two layers of dense electrochromic materials on the surface of the conductive fibers. The flexible electrochromic supercapacitor obtained by the present invention has fast response time, stable cycle stability, long-term color memory and excellent capacitance performance.
[0006] In a first aspect, the present invention provides a method for preparing a flexible electrochromic supercapacitor, comprising the following steps:
[0007] S1, performing surface treatment and hydrophilic treatment on the fiber substrate to obtain a fiber with hydroxyl groups attached to the surface;
[0008] S2, preparing a lithium perchlorate solution, wherein the solvent of the lithium perchlorate solution is propylene carbonate solvent;
[0009] S3, preparing a 3-methylthiophene solution of a predetermined concentration, and adding a predetermined amount of the 3-methylthiophene solution to the lithium perchlorate solution prepared in step S2;
[0010] S4, introducing argon gas into the solution prepared in step S3 to remove oxygen in the solution, thereby obtaining a 3-methylthiophene precursor solution;
[0011] S5, preparing a sodium tungstate solution, wherein the solvent of the sodium tungstate solution is deionized water;
[0012] S6, adding hydrogen peroxide and sulfuric acid to the sodium tungstate solution prepared in step S5 to prepare a tungsten trioxide precursor solution;
[0013] S7, placing the fiber treated in step S1 in the 3-methylthiophene precursor solution prepared in step S4, and using a three-electrode system to perform constant voltage deposition for 45s to 75s, so that 3-methylthiophene is evenly deposited on the surface of the fiber substrate, and a fiber with a surface coated with an electrochromic layer is obtained; the constant voltage deposition process includes the following contents: using the fiber obtained in step S1 as the positive electrode, the platinum electrode as the negative electrode, and the calomel electrode as the reference electrode;
[0014] S8, placing the fiber with the surface coated with the electrochromic layer obtained in step S7 in the tungsten trioxide precursor solution prepared in step S6, and using a three-electrode system to perform constant voltage deposition for 15s to 45s, so that the tungsten trioxide is uniformly deposited on the fiber surface; the constant voltage deposition includes the following contents: using the fiber obtained in step S7 as the positive electrode, the platinum electrode as the negative electrode, and the calomel electrode as the reference electrode;
[0015] S9, completely coating the fiber treated in step S8 with a gel electrolyte, and obtaining the flexible electrochromic supercapacitor after drying.
[0016] Preferably, in step S6, the concentration of sulfuric acid in the tungsten trioxide precursor solution is 0.3-0.6 mol / L, the concentration of hydrogen peroxide is 5-8 mol / L, and the concentration of sodium tungstate is 0.1-0.5 mol / L.
[0017] Preferably, in step S3, the predetermined concentration of 3-methylthiophene is 0.05-0.2 mol / L.
[0018] Preferably, the molar mass ratio of the 3-methylthiophene to the lithium perchlorate is (0.5-2):1.
[0019] Preferably, in step S7, the voltage during the constant voltage deposition process is 2.5-3.5V.
[0020] Preferably, in step S8, the voltage during the constant voltage deposition process is -0.5 to -1V.
[0021] Preferably, in step S5, the concentration of lithium perchlorate is 0.05-0.2 mol / L.
[0022] Preferably, in step S9, the preparation method of the gel electrolyte is: dissolving lithium perchlorate in a propylene carbonate solution, stirring sufficiently, and configuring a LiClO4:PC solution with a concentration of 10wt% to form a liquid electrolyte; then, adding polymethyl methacrylate particles to the liquid electrolyte solution, stirring and heating in a water bath at 80-90°C for 12-24h; the mass of polymethyl methacrylate in the gel electrolyte is 20-30wt% of propylene carbonate.
[0023] Preferably, in step S1, the hydrophilic treatment refers to using the surface-treated fiber as the positive electrode, the platinum electrode as the negative electrode, and the potassium hydroxide solution as the electrolyte, and obtaining the fiber with hydroxyl groups attached to the surface after the electrical treatment; the concentration of the electrolyte potassium hydroxide solution is 2-3 mol / L, the electrical time is 5-6 min, and the voltage is 5-6V.
[0024] In the second aspect, an embodiment of the present application provides a flexible electrochromic supercapacitor, which is prepared by the preparation method described in the aforementioned technical scheme. The flexible electrochromic supercapacitor includes an internal fiber substrate, an electrochromic layer attached to the surface of the fiber substrate, and a gel electrolyte layer coated on the surface of the electrochromic layer; the electrochromic layer includes an organic electrochromic layer and an inorganic electrochromic layer.
[0025] The beneficial effects of the present invention are:
[0026] 1. The preparation method of the flexible electrochromic supercapacitor provided by the present invention comprises the following steps: treating the surface of a conductive fiber substrate and performing a hydrophilic treatment to make the fiber surface clean and attached with hydroxyl groups; placing the treated fibers in a prepared 3-methylthiophene precursor solution and a tungsten trioxide precursor solution in sequence, and electrochemically treating the fibers using a three-electrode system to deposit a dense electrochromic layer on the fiber surface; and finally completely coating the fibers with a gel electrolyte to obtain a flexible electrochromic supercapacitor.
[0027] 2. The flexible electrochromic supercapacitor provided by the present invention uses flexible conductive fibers as substrates, and electrochemically deposits electrochromic materials on the surface of the substrate using a three-electrode system to form a dense electrochromic layer on the surface of the flexible conductive fibers. The electrochromic layer is then completely coated with a gel electrolyte, and the electrochromic fibers are obtained after natural curing. The prepared electrochromic fibers have good flexibility, stable color change performance, excellent color memory performance, and excellent capacitance performance, and have good application prospects in the field of smart wearable materials.
[0028] 3. The flexible electrochromic supercapacitor prepared by the present invention can present different color changes under different voltages, and can also present different colors at different stored energy levels.
[0029] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 This is an electron microscope image of the stainless steel substrate used in Example 1.
[0032] Figure 2 This is an electron microscope image of the stainless steel fiber prepared in Example 1 with 3-methylthiophene and tungsten trioxide grown on the surface.
[0033] Figure 3 This is the CV cycle diagram of the electrochromic supercapacitor prepared in Example 1.
[0034] Figure 4 This is a chronoamperometry cycle test curve of the electrochromic supercapacitor prepared in Example 1.
[0035] Figure 5 This is a GCD test curve diagram of the electrochromic supercapacitor prepared in Example 1.
[0036] Figure 6 This is a color comparison chart of the electrochromic fiber prepared in Example 1 under different voltages.
[0037] Figure 7 Actual pictures of the electrochromic supercapacitor prepared in Example 1 at different voltages. DETAILED DESCRIPTION
[0038] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0040] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0041] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0042] The present invention provides a method for preparing a flexible electrochromic supercapacitor, comprising the following steps:
[0043] S1, performing surface treatment and hydrophilic treatment on the fiber substrate to obtain a fiber with hydroxyl groups attached to the surface;
[0044] The surface treatment is to put the fiber to be treated into a beaker containing anhydrous ethanol solution, ultrasonically vibrate for 10 to 20 minutes, take it out, rinse it with deionized water and dry it to obtain a fiber with a clean surface.
[0045] The hydrophilic treatment is to use the surface treated fiber as the positive electrode, the platinum electrode as the negative electrode, and a potassium hydroxide solution with a concentration of 2 to 3 mol / L as the electrolyte. The power is turned on at a voltage of 5 to 6 V for 5 to 6 minutes to obtain a fiber with a large number of hydroxyl groups attached to the surface.
[0046] S2, preparing a lithium perchlorate solution, wherein the solvent of the lithium perchlorate solution is propylene carbonate solvent;
[0047] Specifically, lithium perchlorate is used as the solute and propylene carbonate is used as the solvent; the concentration of the lithium perchlorate solution is 0.05-0.2 mol / L.
[0048] S3, preparing a 3-methylthiophene solution of a predetermined concentration, and adding a predetermined amount of the 3-methylthiophene solution to the lithium perchlorate solution prepared in step S2;
[0049] Specifically, 0.005-0.02 mol / L of 3-methylthiophene is added to 100 ml of 0.1 mol / L electrolyte (with lithium perchlorate as solute and propylene carbonate as solvent) to obtain a 3-methylthiophene precursor solution, wherein the predetermined concentration of the 3-methylthiophene solution is 0.05-0.2 mol / L.
[0050] The molar mass ratio of 3-methylthiophene to lithium perchlorate is (0.5-2):1.
[0051] S4, introducing argon gas into the solution prepared in step S3 to remove oxygen in the solution, thereby obtaining a 3-methylthiophene precursor solution;
[0052] S5, preparing a sodium tungstate solution, wherein the solvent of the sodium tungstate solution is deionized water; S6, adding hydrogen peroxide and sulfuric acid to the sodium tungstate solution prepared in step S5 to prepare a tungsten trioxide precursor solution;
[0053] Specifically, the precursor solution is a mixed solution including sodium tungstate, hydrogen peroxide and sulfuric acid.
[0054] Among them, the concentration of sodium tungstate is 0.1-0.5 mol / L, the concentration of sulfuric acid is 0.3-0.6 mol / L, and the concentration of hydrogen peroxide is 5-8 mol / L.
[0055] S7, placing the fiber treated in step S1 in the 3-methylthiophene precursor solution prepared in step S4, using a three-electrode system to perform constant voltage deposition for 45s to 75s, so that 3-methylthiophene is evenly deposited on the surface of the fiber substrate, and a fiber with a surface coated with an electrochromic layer is obtained; the constant voltage deposition process includes the following contents: the fiber obtained in step S1 is used as the positive electrode, the platinum electrode is used as the negative electrode, and the calomel electrode is used as the reference electrode; the voltage during the constant voltage deposition treatment is 2.5 to 3.5V.
[0056] S8, placing the fiber with the surface coated with the electrochromic layer obtained in step S7 in the tungsten trioxide precursor solution prepared in step S6, and using a three-electrode system to perform constant voltage deposition for 15s to 45s, so that the tungsten trioxide is evenly deposited on the fiber surface; the constant voltage deposition includes the following contents: the fiber obtained in step S7 is used as the positive electrode, the platinum electrode is used as the negative electrode, and the calomel electrode is used as the reference electrode; the voltage during the constant voltage deposition treatment is -0.5 to -1V.
[0057] S9, completely coating the fiber treated in step S8 with a gel electrolyte, and obtaining the flexible electrochromic supercapacitor after drying.
[0058] Specifically, the preparation method of the gel electrolyte is as follows: propylene carbonate solution containing 8 to 12 wt % of lithium perchlorate is mixed with 20 to 30 wt % of polymethyl methacrylate, and the mixture is heated in a water bath at 80 to 90° C. with stirring for 12 hours to prepare the gel electrolyte.
[0059] The present invention first electrochemically deposits an organic high molecular polymer 3-methylthiophene to deposit a uniform electrochromic layer on the fiber surface, and then electrochemically deposits a layer of inorganic metal oxide tungsten trioxide on the surface to form an ion storage layer, thereby obtaining a flexible electrochromic supercapacitor with good flexibility, fast response speed and obvious color change.
[0060] The present invention also provides a flexible electrochromic supercapacitor, which is prepared by the above-mentioned preparation method, and the flexible electrochromic supercapacitor includes an internal fiber substrate, an electrochromic layer attached to the surface of the fiber substrate, and a gel electrolyte layer coated on the surface of the electrochromic layer. The electrochromic layer includes an organic electrochromic layer and an inorganic electrochromic layer.
[0061] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0062] Example 1
[0063] This embodiment provides a method for preparing a flexible electrochromic supercapacitor, comprising the following steps:
[0064] S1, put the stainless steel fiber into anhydrous ethanol for ultrasonic cleaning for 15 minutes. After ensuring that it is clean, the cleaned fiber is used as the anode and the platinum electrode is used as the cathode. It is placed in a 2.5 mol / L potassium hydroxide solution and a voltage of 5V is passed for 2 minutes (hydrophilic treatment). The obtained fiber is dried at room temperature and stored for later use;
[0065] S2, add 0.01 mol of lithium perchlorate into 100 ml of propylene carbonate solvent to prepare a 0.1 mol / L electrolyte.
[0066] S3, prepare 3-methylthiophene with a concentration of 0.1 mol / L, add 0.01 mol / L of 3-methylthiophene to 0.1 mol / L of electrolyte (with lithium perchlorate as solute and propylene carbonate as solvent) to obtain a 3-methylthiophene precursor solution. The molar mass ratio of 3-methylthiophene to the lithium perchlorate is 1:1.
[0067] S4, passing argon gas into the solution prepared in step S3 for 30 minutes to remove oxygen in the solution, thereby obtaining a 3-methylthiophene precursor solution;
[0068] S5, prepare 0.2 mol / L sodium tungstate solution, the solvent is deionized water;
[0069] S6, heating the sodium tungstate solution prepared in step S5 in a water bath for 30 minutes, adding 0.5 mol / L concentrated sulfuric acid after cooling, and then adding hydrogen peroxide dropwise after the reaction is complete until the sodium tungstate solution is clear, thereby obtaining a tungsten trioxide precursor solution.
[0070] S7, using the fiber treated in step S1 as a working electrode, a platinum electrode as a counter electrode, and a calomel electrode as a reference electrode to form a three-electrode system, and placing it in the 3-methylthiophene precursor solution obtained in step S4. Apply a constant voltage of 3V for 45s through an electrochemical workstation to obtain a stainless steel fiber with a surface coated with an electrochromic layer.
[0071] S8, placing the stainless steel fiber with a surface coated with an electrochromic layer obtained in step S7 into the tungsten trioxide precursor solution prepared in step S6, applying a constant voltage of -0.7V, electrochemically treating for 30s, rinsing with deionized water, and naturally drying to obtain the stainless steel electrochromic fiber.
[0072] S9, drying lithium perchlorate at 120°C for 24 hours, and drying polymethyl methacrylate particles at 80°C for 24 hours; dissolving a certain amount of lithium perchlorate in a propylene carbonate solution, stirring thoroughly, and preparing a 10wt% LiClO4:PC solution to form a liquid electrolyte; adding polymethyl methacrylate particles to the above electrolyte solution, and continuously stirring at 85°C for 12 hours to form a gel electrolyte;
[0073] Take the fiber treated in step S8 and immerse it in the gel electrolyte, leaving 5mm at one end of the fiber so that the rest is completely covered by the gel electrolyte, and then use the stainless steel fiber treated in step S1, leaving 5mm so that the rest is covered by the gel electrolyte, and place the two fibers in parallel to obtain a flexible electrochromic supercapacitor. Figure 7 As shown. The left picture is an optical photo of a capacitor with a voltage of -0.4V, and the right picture is a photo of a capacitor with a voltage of 0.8V. This shows that electrochromic supercapacitors can have different color changes at different voltages.
[0074] See also Figure 1 , which is an electron microscope image of the stainless steel fiber substrate used in Example 1. It can be seen from the image that the stainless steel fiber substrate has a smooth fiber surface structure before being treated.
[0075] Figure 2 This is a picture of the stainless steel fiber with 3-methylthiophene and tungsten trioxide grown on the surface in Example 1. It can be seen that the surface is coated with a dense layer of electrochromic material.
[0076] See also Figure 3, which is the result of CV cycle performance test of the stainless steel electrochromic fiber prepared in Example 1. The curve shows the redox peak of the electrochromic supercapacitor and indicates that the redox of the electrochromic supercapacitor is reversible.
[0077] See also Figure 4 The figure shows the chronoamperometry cycle test curve of the electrochromic supercapacitor prepared in Example 1. The maximum current of the electrochromic supercapacitor remained basically unchanged within 100 cycles, and was always maintained at about 6 mA. This shows that the electrochromic supercapacitor prepared in this example has good electrochemical stability.
[0078] See also Figure 5 As shown in FIG. 1 , the GCD charge-discharge curve of the electrochromic supercapacitor prepared in Example 1 is shown. From the curve, it can be seen that at different current densities (5A / g, 10A / g, 50A / g, 100A / g), the voltage can reach 1V in a very short time, indicating that it has good capacitance performance.
[0079] See also Figure 6 As shown, the optical photos of different colors of the electrochromic supercapacitor prepared in Example 1 at different voltages are shown. It can be seen that at a voltage of 0.8V, the electrochromic supercapacitor is black (left picture); at a voltage of -0.4V, the electrochromic supercapacitor is red (right picture). This shows that the prepared electrochromic supercapacitor has different color changes at different voltages.
[0080] Comparative Example 1
[0081] Comparative Example 1 provides a method for preparing a flexible electrochromic supercapacitor. Compared with Example 1, the difference is that steps S2-S4 and step S7 are not performed; that is, a 3-methylthiophene precursor solution is not prepared, and the fiber is not electrochemically treated with the 3-methylthiophene precursor solution. The rest is roughly the same as Example 1 and will not be repeated here.
[0082] Comparative Example 2
[0083] Comparative Example 2 provides a method for preparing a flexible electrochromic supercapacitor. Compared with Example 1, the difference is that steps S5, S6 and S8 are not performed; that is, a sodium tungstate solution precursor solution is not prepared, and the fiber is not electrochemically treated with a tungsten trioxide precursor solution. The rest is roughly the same as Example 1 and will not be repeated here.
[0084] Examples 2-3 and Comparative Examples 3-6
[0085] The preparation method of the flexible electrochromic supercapacitor provided in Examples 2-3 and Comparative Examples 3-6 is different from that in Example 1, in that the concentration of 3-methylthiophene in step S3, the molar mass ratio of 3-methylthiophene to lithium perchlorate, and the concentration of sodium tungstate in step S5 are changed; the details are shown in the following table; the rest are roughly the same as in Example 1 and will not be repeated here.
[0086]
[0087] The flexible electrochromic supercapacitors prepared in Examples 1-3 and Comparative Examples 1-6 were tested for electrochromic performance and capacitance performance, and the results are shown in the following table:
[0088] Specific capacitance (F / g) Coloring time(s) Bleaching time(s) Example 1 85.6 0.60 0.29 Comparative Example 1 137.5 2.17 2.31 Comparative Example 2 ~ 0.86 0.65 Example 2 83.2 0.64 0.35 Comparative Example 3 24.6 1.47 1.84 Comparative Example 4 34.7 1.25 1.53 Example 3 91.8 0.81 0.74 Comparative Example 5 ~ 1.13 0.94 Comparative Example 6 116.4 3.12 2.83
[0089] It can be seen from Comparative Example 2 that only one layer of 3-methylthiophene will cause the electrochromic supercapacitor to have no capacitor performance. This is because it is difficult for a high molecular polymer to have capacitor performance.
[0090] As can be seen from Comparative Example 1, the electrochromic supercapacitor with only one layer of tungsten trioxide has a significantly longer electrochromic time. This is because the surface of tungsten trioxide is dense, ions intercalate slowly, and the coloring and bleaching time is long.
[0091] According to Examples 1-3 and Comparative Examples 3-6, changing the concentration of 3-methylthiophene or changing the concentration of sodium tungstate will result in different thicknesses of the electrochromic layer obtained after electrochemical treatment, resulting in a decrease in its electrochromic performance or capacitor performance.
[0092] Specifically, it can be seen from Comparative Example 3 that when the concentration of 3-methylthiophene is lower than 0.05 mol / L, due to the low concentration, too little electrochromic material is formed on the surface of the substrate, resulting in a decrease in its capacitance performance and an increase in the electrochromic coloring / bleaching time.
[0093] It can be seen from Comparative Example 4 that when the concentration of 3-methylthiophene is higher than 0.2 mol / L, the concentration of the precursor solution is too high, resulting in the electrode material formed on the surface of the substrate being too thick, affecting its capacitance performance and electrochromic time.
[0094] It can be seen from Comparative Example 5 that when the concentration of sodium tungstate is lower than 0.1 mol / L, too little tungsten trioxide is deposited on the surface of the substrate, which affects its capacitance performance. The ions cannot be well stored in the electrode material, resulting in a decrease in its capacitance performance.
[0095] It can be seen from Comparative Example 6 that when the concentration of sodium tungstate is higher than 0.5 mol / L, an excessively thick layer of tungsten trioxide material is deposited on the surface of the substrate, which slows down the ion intercalation and prolongs the electrochromic time.
[0096] Examples 4-7 and Comparative Examples 7-14
[0097] The preparation method of the flexible electrochromic supercapacitor provided in Examples 4-7 and Comparative Examples 7-14 is different from that in Example 1 in that the voltage and time of the constant voltage deposition treatment in the 3-methylthiophene precursor solution in step S7 and the voltage and time of the constant voltage deposition treatment in the tungsten trioxide precursor solution in step S8 are changed; the details are shown in the following table; the rest are roughly the same as in Example 1 and will not be repeated here.
[0098]
[0099]
[0100] The flexible electrochromic supercapacitors prepared in Examples 1, 4-7 and Comparative Examples 7-14 were tested for electrochromic performance and capacitance performance, and the results are shown in the following table:
[0101] Specific capacitance (F / g) Coloring time(s) Bleaching time(s) Example 1 85.6 0.60 0.29 Example 4 87.3 0.63 0.41 Comparative Example 7 97.3 1.64 1.24 Comparative Example 8 ~ ~ ~ Example 5 78.3 0.54 0.47 Comparative Example 9 ~ 0.55 0.27 Comparative Example 10 133.9 2.75 2.36 Example 6 80.3 0.74 0.42 Comparative Example 11 ~ 1.87 1.66 Comparative Example 12 56.2 0.94 0.73 Example 7 90.3 0.96 0.72 Comparative Example 13 20.3 0.91 0.76 Comparative Example 14 104.3 2.64 1.99
[0102] It can be seen from the above table that changing the voltage and treatment time of the electrochemical treatment of the fiber in the precursor solution will affect the electrochromic performance and capacitance performance of the prepared flexible electrochromic supercapacitor.
[0103] Specifically, when the voltage of the electrochemical treatment is too low, the electrochromic layer cannot be deposited on the fiber; when the voltage is too high, the electrochromic layer will be too thick. That is, by changing the thickness of the electrochromic layer on the surface of the fiber, its electrochromic performance is affected. Changing the electrochemical treatment time of the fiber in the precursor solution, if the treatment time is too short, the electrochromic layer will be too thin, resulting in poor capacitor performance; if the treatment time is too long, the electrochromic layer will be too thick, which will prolong the coloring and bleaching time.
[0104] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing a flexible electrochromic supercapacitor, characterized in that: The following steps are involved: S1, performing surface treatment and hydrophilic treatment on the fiber substrate to obtain a fiber with hydroxyl groups attached to the surface; S2, preparing a lithium perchlorate solution, wherein the solvent of the lithium perchlorate solution is propylene carbonate solvent; S3, preparing a 3-methylthiophene solution of a predetermined concentration, and adding a predetermined amount of the 3-methylthiophene solution to the lithium perchlorate solution prepared in step S2; S4, introducing argon gas into the solution prepared in step S3 to remove oxygen in the solution, thereby obtaining a 3-methylthiophene precursor solution; S5, preparing a sodium tungstate solution, wherein the solvent of the sodium tungstate solution is deionized water; S6, adding hydrogen peroxide and sulfuric acid to the sodium tungstate solution prepared in step S5 to prepare a tungsten trioxide precursor solution; S7, placing the fiber treated in step S1 in the 3-methylthiophene precursor solution prepared in step S4, and using a three-electrode system to perform constant voltage deposition for 45s to 75s, so that 3-methylthiophene is evenly deposited on the surface of the fiber substrate, and a fiber with a surface coated with an electrochromic layer is obtained; the constant voltage deposition process includes the following contents: using the fiber obtained in step S1 as the positive electrode, the platinum electrode as the negative electrode, and the calomel electrode as the reference electrode; S8, placing the fiber with the surface coated with the electrochromic layer obtained in step S7 in the tungsten trioxide precursor solution prepared in step S6, and using a three-electrode system to perform constant voltage deposition for 15s to 45s, so that the tungsten trioxide is uniformly deposited on the fiber surface; the constant voltage deposition includes the following contents: using the fiber obtained in step S7 as the positive electrode, the platinum electrode as the negative electrode, and the calomel electrode as the reference electrode; S9, completely coating the fiber treated in step S8 with a gel electrolyte, and obtaining the flexible electrochromic supercapacitor after drying.
2. The method for preparing a flexible electrochromic supercapacitor according to claim 1, characterized in that: In step S6, the concentration of sulfuric acid in the tungsten trioxide precursor solution is 0.3-0.6 mol / L, the concentration of hydrogen peroxide is 5-8 mol / L, and the concentration of sodium tungstate is 0.1-0.5 mol / L.
3. The method for preparing a flexible electrochromic supercapacitor according to claim 1, characterized in that: In step S3, the predetermined concentration of 3-methylthiophene is 0.05-0.2 mol / L.
4. The method for preparing a flexible electrochromic supercapacitor according to claim 1, characterized in that: The molar mass ratio of the 3-methylthiophene to the lithium perchlorate is (0.5-2):
1.
5. The method for preparing a flexible electrochromic supercapacitor according to claim 1, characterized in that: In step S7, the voltage during the constant voltage deposition process is 2.5-3.5V.
6. The method for preparing a flexible electrochromic supercapacitor according to claim 1, characterized in that: In step S8, the voltage during the constant voltage deposition process is -0.5 to -1V.
7. The method for preparing a flexible electrochromic supercapacitor according to claim 1, characterized in that: In step S5, the concentration of lithium perchlorate is 0.05-0.2 mol / L.
8. The method for preparing a flexible electrochromic supercapacitor according to claim 1, characterized in that: In step S9, the preparation method of the gel electrolyte is as follows: lithium perchlorate is dissolved in a propylene carbonate solution, and the solution is stirred sufficiently to form a 10wt% LiClO4:PC solution to form a liquid electrolyte; then, polymethyl methacrylate particles are added to the liquid electrolyte solution, and stirred and heated in a water bath at 80 to 90° C. for 12 to 24 hours; the mass of polymethyl methacrylate in the gel electrolyte is 20 to 30wt% of the propylene carbonate.
9. The method for preparing a flexible electrochromic supercapacitor according to claim 1, characterized in that: In step S1, the hydrophilic treatment refers to using the surface treated fiber as the positive electrode, the platinum electrode as the negative electrode, and the potassium hydroxide solution as the electrolyte, and obtaining the fiber with hydroxyl groups attached to the surface after the electrical treatment; the concentration of the electrolyte potassium hydroxide solution is 2-3 mol / L, the electrical time is 5-6 min, and the voltage is 5-6V.
10. A flexible electrochromic supercapacitor, characterized in that: The flexible electrochromic supercapacitor is prepared by the preparation method described in any one of claims 1 to 9, comprising an internal fiber substrate, an electrochromic layer attached to the surface of the fiber substrate, and a gel electrolyte layer coated on the surface of the electrochromic layer; the electrochromic layer comprises an organic electrochromic layer and an inorganic electrochromic layer.
Citation Information
Patent Citations
Fiber-shaped flexible electrochromic device and preparation method thereof
CN102759835A
Preparation method of novel fast-response high-contrast electrochromic device
CN104216192A
High-color-contrast electrochromic device and method of assembling the same
CN110262152A
Ultrafast-response overcharge-prevention electrochromic device and preparation method thereof
CN110764331A
Electrochromic fiber and preparation method thereof
CN115652612A